Modeling algorithm for dynamic generalized body cavity. Issue 1 (1st January 2018) - Mo, Jianqing; He, Hanwu; Li, Jinfang; Chen, Heen
Abstract: For the purpose of preoperative planning, this paper proposed a modeling algorithm for automatically creating the dynamic model of the generalized body cavity. The algorithm includes two phases. One is the static phase in which the initial cavity model is created from the cross sections; the other is the dynamic phase for modeling the dynamic cavity. In the static phase, the parallel cross sections are generated through slicing the organs enclosing the cavity; then construct the LBCs, and generate the uniform grids; and then create the hexahedron voxels according to the uniform grids; at last, post-processing is used to get the final cavity model represented by triangular meshes. In the dynamic phase, the cavity models at different moments are gained by applying the anchor connection method. We took the human articular cavity as an example to verify the proposed algorithm, and the experimental results showed that the proposed algorithm is effective.